Wafer-Scale Growth of Sb2Te3Films via Low-Temperature Atomic Layer Deposition for Self-Powered Photodetectors - Yang, Jun; Li, Jianzhu; Bahrami, Amin; Nasiri, Noushin; Lehmann, Sebastian; Cichocka, Magdalena Ola; Mukherjee, Samik; Nielsch, Kornelius (ACS Applied Materials and Interfaces, 2022)
In this work, we demonstrate the performance of a silicon-compatible, high-performance, and self-powered photodetector. A wide detection range from visible (405 nm) to near-infrared (1550 nm) light was enabled by the vertical p-n heterojunction between the p-type antimony telluride (Sb2Te3) thin film and the n-type silicon (Si) substrates. A Sb2Te3film with a good crystal quality, low density of extended defects, proper stoichiometry, p-type nature, and excellent uniformity across a 4 in. wafer was achieved by atomic layer deposition at 80 °C using (Et3Si)2Te and SbCl3as precursors. The processed photodetectors have a low dark current (∼20 pA), a high responsivity of (∼4.3 A/W at 405 nm and ∼150 mA/W at 1550 nm), a peak detectivity of ∼1.65 × 1014Jones, and a quick rise time of ∼98 μs under zero bias voltage. Density functional theory calculations reveal a narrow, near-direct, type-II band gap at the heterointerface that supports a strong built-in electric field leading to efficient separation of the photogenerated carriers. The devices have long-term air stability and efficient switching behavior even at elevated temperatures. These high-performance and self-powered p-Sb2Te3/n-Si heterojunction photodetectors have immense potential to become reliable technological building blocks for a plethora of innovative applications in next-generation optoelectronics, silicon-photonics, chip-level sensing, and detection.
CRIS-Team Scopus Importer:2023-03-20
Keywords: atomic layer deposition; heterostructure photodetector; high responsivity; Sb; self-powered